Use of Resveratrol Self-Emulsifying Systems in T/C28a2 Cell Line as Beneficial Effectors in Cellular Uptake and Protection Against Oxidative Stress-Mediated Death - Le Clanche, Solenn; Cheminel, Tristan; Rannou, François; Bonnefont-Rousselot, Dominique; Borderie, Didier; Charrueau, Christine (Frontiers in Pharmacology, 2018)
Osteoarthritis (OA) is the most prevalent rheumatic disease in the world. Although its etiology is still unknown, one of the key processes in OA progression and development is oxidative stress. In this context, resveratrol, a well-known anti-oxidant from the stilbene family, could be of particular interest in future OA therapeutic strategies. However, currently, because of its low bioavailability, use of resveratrol in human health is very limited. In this study, we tested two resveratrol self-emulsifying systems previously developed in our laboratory in order to determine if they could improve cellular uptake of resveratrol in a human immortalized chondrocytic cell line (T/C28a2) and enhance protection against oxidative stress. Our results showed that resveratrol self-emulsifying systems were able first to increase cellular tolerance towards resveratrol, thus to decrease resveratrol intrinsic cellular toxicity allowing the use of higher concentrations; second, to increase resveratrol uptake in membrane and intracellular fractions; and finally to improve protection against oxidative stress-mediated death in human immortalized chondrocytic cell line T/C28a2. These data suggest that new formulations of resveratrol could be considered as potential beneficial effectors in future OA treatments.